Thesis and Dissertation Copyright Instruction for Grad Students: What They Should Know and Why They Should Care. - Schuler, Andrea (Tufts University. Tisch Library., 2019)
This chapter lays out specific copyright issues that arise with theses and dissertations and provides a framework for contextualizing instruction in practical, real‐life applications that are meaningful for students: what they should know and why they should care. It considers copyright instruction for graduate students and basic copyright principles important for all instructors. It then focuses on the rights of the student author, considerations in using others' work, and decisions about open access to the finished thesis or dissertation. Example exercises for teaching copyright principles, fair use, and evaluating an author's contract are also included.